Aplikasi Kumer-Math Berbasis Pembelajaran Diferensiasi Terhadap Kemampuan Berpikir Kreatif Pada Materi Perbandingan Trigonometri - Rinda Sari; Hartono; Muhammad Firdaus (LPD IKIP PGRI Pontianak, 2024)
This research aims to produce learning media in the form of Android applications that achieve valid, practical and effective criteria so that they are suitable for use. This research uses Research and Development (R&D) methodology. The steps for developing this application use the ADDIE model which stands for analysis, design, development, implementation and evaluation. The subjects in this research were class X SMA Negeri 1 Mempawah Hilir students. The instruments used in this research were media and material expert validation sheets, student and teacher response questionnaires, and posttests. The research results related to validity reached a validity level in the